PROBLEMS OF MARKET MODERNIZATION DURING THE NEW ECONOMIC POLICY (1921-1929) (ON THE MATERIALS OF THE DON AND THE KUBAN) - Yuriy Yakhutl (Гуманитарные и юридические исследования)
The new economic policy adopted at the X Congress of the RCP (b) in 1921 remains one of the problematic issues in the history of Russia. It is of interest as it provided the possibility of using market methods in combination with planned tools in the process of economic modernization. The problems of the transition period remain relevant at the present stage of development of the Russian society, as it is important to know and be able to use the experience of the past. Economic reforms that could combine market methods with government regulation policies are becoming relevant. The level of market relations in the agricultural sector of the economy in the NEP system was determined by the degree of activity of the state in the implementation of food policy, land relations and confrontation of the Soviet power of the wealthy part of the peasantry. The new economic policy in the South of Russia, where special forms of land use prevailed and class contradictions existed, were implemented under the strict control of the state, which did not come from economic expediency and ideological attitudes. The formation of new land relations, administrative reforms carried out during the 1920s in the Cossack regions of the South pursued the goal of maximum weakening of the influence of the Cossacks on the policy of the Bolsheviks. It should be noted that the level of development of Cossack farms exceeded the national average indicators. In modern historical science, a special place is given to the regional component, the formation of new historical knowledge, the study of regional characteristics. Modern historians are interested in documents to which access has been restricted for certain political and ideological reasons. Archival materials of the Don and the Kuban of the 1920s have now become the object of active study. It should be noted that after 1991, the methodological approaches have changed in many ways; it is safe to say that researchers have lost interest in the Marxist model of the new economic policy and, in many respects, research is based on multidirectional theoretical findings in the assessment of the NEP. Market mechanisms in the NEP system worked under the control of the state, but were not guaranteed by the current legislation and were ignored as the confrontation between individual private peasant-cossack farms and the political interests of the Bolsheviks grew.